Effect of crystal orientation and texture on fatigue crack evolution in high strength steel welds. (August 2015) - Azar, Amin S.; Svensson, Lars-Erik; Nyhus, Bård
Highlights: Effects of crystallographic features on fatigue failure in high strength welds were investigated. Mechanism for crystal rotation assisted cracking was proposed. Schmid factor and Taylor factor variations were related to the fatigue crack behavior. Grain boundary analyses were performed to find the fatigue susceptible boundaries. Welding heat direction was found influential on fatigue crack trajectory. Abstract: In the present study, electron backscattered diffraction is used to analyze the fatigue crack evolution in a high strength steel weld that was loaded cyclically in the plastic regime. Three prominent regions of a fatigue crack are investigated separately: crack tip, crack trajectory and crack initiation. Taylor and Schmid factors are mapped with respect to the defined loading matrix. Possible effective mechanisms are proposed based on the local plasticity properties like lattice rotation and misorientation. The analyses of the crack tip and trajectory regions show that although the critical resolved shear stresses in some regions are low, small deformation resistance of these regions can compromise the dislocation immobility and cause local fracture. It is shown that if the crack grows transgranularly, at least one side of the crack may show low lattice rotation or strain equivalent values, which indicates the relaxation of elastic stresses after fracture. The crack initiation is determined to be dominantly controlled by transcrystalline mechanism of initiation that takes place under plastic loading conditions. It is also shown that the secondary 〈 1 2 3 〉 { 1 1 1 ¯ } type of slip systems were the most activated under such loading conditions.